The end of the free market : who wins the war between states and corporations? - Bremmer, Ian, 1969- (New York, N.Y. : Portfolio, 2010)
This work details the growing phenomenon of state capitalism, a system in which governments drive local economies through ownership of market-dominant companies. This trend, Bremmer argues, threatens America's competitive edge and the conduct of free markets everywhere.
Includes bibliographical references (p. 205-221) and index.
Keywords: Capitalism -- Communist countries; Capitalism -- Developing countries; Government ownership -- Communist countries; Government ownership -- Developing countries; Communist countries -- Economic policy